Field–Frequency-Dependent Non-linear Rheological Behavior of Magnetorheological Grease Under Large Amplitude Oscillatory Shear - Wang, Huixing; Chang, Tianxiao; Li, Yancheng; Li, Shaoqi; Zhang, Guang; Wang, Jiong (Frontiers in Materials, 2021)
This paper investigates the influence of frequency on the field-dependent nonlinear rheology of magnetorheological (MR) grease under large amplitude oscillatory shear. Firstly, the large amplitude oscillatory shear test with different driving frequencies are conducted on the MR grease at four magnetic fields, and the storage and loss moduli under the frequency of 0.1Hz, 0.5Hz, 1Hz and 5Hz are compared to obtain an overall understanding of the frequency-dependent viscoelastic behavior of MR grease. Built on this, the 3D Lissajous curves and decomposed stress curves under two typical frequencies are depicted, respectively, to provide the nonlinear elastic and viscous behavior. Finally, the elastic and viscous measures containing higher harmonics from FT-Chebyshev analysis are used to quantitively interpret the influence of the frequency on nonlinear rheology of MR grease, i.e., strain stiffening (softening), shear thickening (thinning), under large amplitude oscillatory shear with different magnetic field. It is found that under the application of the magnetic field, the onset of the nonlinear behavior of MR grease is frequency-dependent. However, when the shear strain amplitude increases into the post-yield region, the nonlinear rheology of MRG-70 is not affected by the oscillatory frequency.